السلوك الاجتماعي المدرسي وعلاقته بمفهوم الذات - بلان كمال; الحلح سمر وليد (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يهدف البحث الحالي إلى الكشف عن العلاقة بين السلوك الاجتماعي المدرسي ومفهوم الذات لدى عينة من تلاميذ الصف الثاني الثانوي، ودراسة الفروق بين الجنسين (الذكور والإناث) في متغيرات البحث(السلوك الاجتماعي المدرسي، مفهوم الذات). وتكون مجتمع البحث من مدارس التعليم الثانوي الحكومية في منطقة صحنايا، وهم طلبة الصف الثاني الثانوي(15- 17)سنة، وقد تم سحب العينة بشكل عشوائي والتي بلغت(90) طالباً وطالبة (45 ذكور+ 45 إناث)، واستخدمت الباحثة الأدوات التالية: 1- مقياس السلوك الاجتماعي المدرسي، 2- مقياس مفهوم الذات بعد أن قامت باختبار صدقهما وثباتهما وقد اتبعت الباحثة المنهج الوصفي التحليلي وذلك لمناسبته لطبيعة البحث، وقد وضعت مجموعة من الفروض وأتت النتائج كما يلي: 1- وجود علاقة دالة إحصائياً بين السلوك الاجتماعي المدرسي ومفهوم الذات لدى عينة البحث. 2- وجود فروق ذات دلالة إحصائية في السلوك الاجتماعي المدرسي تبعاً لمتغير الجنس لصالح عينة الذكور. 3- وجود فروق ذات دلالة إحصائية في مفهوم الذات تبعاً لمتغير الجنس لصالح عينة الذكور. وفي ضوء هذه النتائج قدمت الباحثة مجموعة من المقترحات كان أهمها إجراء المزيد من الدراسات والبحوث حول السلوك الاجتماعي المدرسي وعلاقته ببعض المتغيرات النفسية في المراحل التعليمية المختلفة (الابتدائية، الجامعية) وضرورة وضع برامج إرشادية تهدف إلى إكساب المراهقين الأساليب الصحيحة لتعلم السلوكيات الاجتماعية المدرسية الصحيحة والتي تؤدي إلى تنمية مفهوم ذات إيجابي. This research aims at present to detect the relationship between school social behavior and self-concept among a sample of students in Second graders secondary, and the study of the differences between the gender (male and female) in the search variables (school social behavior, self-concept). And the research community schools of secondary education governmental organizations in the area Sehnaya, who are students of second grade secondary school (15-17 years), have been withdrawn sample randomly, which amounted to (90) students (45 males + 45 females), and the researcher used the following tools: 1 – a measure of school social behavior, 2 - self-concept scale, after that she has tested Validity and reliability, The researcher followed the descriptive analytical method so as to its relevance to the nature of the research،she has developed a set of hypotheses and Results came as following:1- There is a statistically significant relationship between the school social behavior and self-concept among the sample search.2- There were statistically significant differences in the school social behavior depending on gender for the sample of the male.3- There are statistically significant differences in self-concept depending on the gender for the sample of the male. In light of these findings researcher presented a set of proposals the most important was further studies and research on the school social behavior and its relationship to some psychological variables in the various educational stages (elementary, university) and the need to develop outreach programs designed to give teenagers the proper methods to learn correct school social behaviors and that lead to develop a positive self-concept.